Inuit, Tuberculosis, and Political Determinants of Health - Mrozewski, Josephine Catherine (2022)
Tuberculosis is one of humanity's most ancient and deadly diseases. It is largely curable, but its long co-evolution with humans has given it distinctive characteristics that make it hard to control or eradicate. The persistence of tuberculosis is usually attributed to social determinants of health. Yet, history shows that political determinants are more fundamental to its epidemiology. While tuberculosis is indeed shaped by social factors, along with biomedical and sometimes geographic factors, its distinctiveness makes it an especially expensive disease. This in turn makes it political, as decisions are made on how or even whether to allocate resources to treat it. Political dynamics are clearly seen in the history of tuberculosis among Inuit in Canada. Inuit bear a burden of disease among the highest in the world. The burden has lasted for more than a century, but it has not been uniform. Political factors shaped the history into four periods, each with a distinctive manifestation of tuberculosis. The most clear illustration of underlying forces comes in the most anomalous period, starting in the late 1960s, which centred on a unique project in Frobisher Bay. Inuit were given leading-edge treatments locally, and disease rates dropped dramatically. Yet the project was quickly cancelled. The factors behind the project and its cancellation are examined through a cross-disciplinary approach, drawing on archival records, social science and scientific writing, and recent genomic studies. These demonstrate that political determinants of health are the "determinants of determinants" of tuberculosis. Graduate 2023-08-30